Proceedings of the Ocean Drilling Program 1992
DOI: 10.2973/odp.proc.sr.123.160.1992
|View full text |Cite
|
Sign up to set email alerts
|

Petrology, Geochemistry, and Mineralogy of the Early Cretaceous Evolved N-MORB from Sites 765 and 766, Eastern Indian Ocean

Abstract: The Early Cretaceous basaltic rocks obtained from Sites 765 and 766 in the eastern Indian Ocean floor were mostly iron-rich normal mid-ocean ridge basalts (N-MORB), which were derived from a depleted mantle source having strongly light rare earth element (LREE)-depleted rare-earth patterns and a high titanium/zirconium (Ti/Zr) ratio. Basaltic rocks in the upper part of the Site 765 basement section include megacrysts and gabbroic fragments of widely varying mineral chemistry. These megacrysts range from An 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Thus, it seems unlikely that significant amounts of eclogite melting (>15%) were involved in the Exmouth mantle plume, even when considering higher values for the thermal expansion coefficient (a) (Schutt and Lesher, 2006). Limited sampled magmatism at ODP Site 766 provides evidence for low-pressure fractionation of plagioclase and clinopyroxene (cumulate gabbro; Ludden and Dionne, 1992), consistent with the underplating theory (Farnetani et al, 1996), though a normal oceanic source cannot be completely ruled out (Ishiwatari, 1992). Other dredge samples from the region are highly weathered (Sayers et al, 2002) and unsuitable for detailed geochemistry interpretation.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, it seems unlikely that significant amounts of eclogite melting (>15%) were involved in the Exmouth mantle plume, even when considering higher values for the thermal expansion coefficient (a) (Schutt and Lesher, 2006). Limited sampled magmatism at ODP Site 766 provides evidence for low-pressure fractionation of plagioclase and clinopyroxene (cumulate gabbro; Ludden and Dionne, 1992), consistent with the underplating theory (Farnetani et al, 1996), though a normal oceanic source cannot be completely ruled out (Ishiwatari, 1992). Other dredge samples from the region are highly weathered (Sayers et al, 2002) and unsuitable for detailed geochemistry interpretation.…”
Section: Discussionmentioning
confidence: 53%
“…The absence of a negative Nb anomaly argues against IAT identification. MORB with negative correlation between incompatible elements and FeO*/MgO have been reported from the eastern Indian Ocean by Ishiwatari (1992), who concluded that the unusual negative correlation can be attributed to heterogeneity in the source mantle in terms of the FeO*/MgO ratio. Thus, it is concluded here that N‐type greenstones originated in the ocean floor basalt that constituted the normal oceanic crust (N‐MORB) mixed blocks.…”
Section: Discussionmentioning
confidence: 80%
“…For a comparison, fields of oceanic gabbros, MORB (phenocrysts), Troodos, IAT (phenocrysts of island arc tholeiite) are also shown. Data sources: oceanic gabbros: Beard [1986] and Juteau and Maury [1999], Troodos: Thy [1987], MORB and IAT: Ishiwatari [1992], Arc Type I and II and tholeiitic layered intrusions: Beard [1986], Haymiliyah, Salahi, Rustaq and Ragmi: Lachize et al [1996]. All rocks plot on a similar trend within the oceanic gabbro and MORB phenocryst fields except for those of the Fizh-South complex.…”
Section: Clinopyroxene Compositionmentioning
confidence: 99%